2016
DOI: 10.1292/jvms.16-0080
|View full text |Cite
|
Sign up to set email alerts
|

<i>Theileria annulata</i> seroprevalence among different cattle breeds in Rajshahi Division, Bangladesh

Abstract: An epidemiological survey of Theileria annulata infection was undertaken in a cattle population in Rajshahi Division, Bangladesh. The local cattle breeds from the area (North Bengal Gray and Deshi) and crosses between the local breeds and Holstein cattle were predominantly screened. In total, 192 cattle serum samples were collected in two areas of Rajshahi Division, the Rajshahi District (n=147) and Natore District (n=45). The samples were screened with an enzyme-linked immunosorbent assay using T. annulata su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Limited studies also have performed serological examination to confirm the tentative diagnosis of infections (Ali et al, 2016;Rahman, Sumon et al, 2015). However, these studies are only reliable for the diagnosis of acute cases but have limited value in subclinical cases due to low parasitaemia (Alim et al, 2012;Hosen et al, 2020;Samad et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited studies also have performed serological examination to confirm the tentative diagnosis of infections (Ali et al, 2016;Rahman, Sumon et al, 2015). However, these studies are only reliable for the diagnosis of acute cases but have limited value in subclinical cases due to low parasitaemia (Alim et al, 2012;Hosen et al, 2020;Samad et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers identified bovine piroplasms using microscopic examination for epidemiological investigation (Al Mahmud et al., 2015 ; Chowdhury, Hossain et al., 2006 ). Limited studies also have performed serological examination to confirm the tentative diagnosis of infections (Ali et al., 2016 ; Rahman, Sumon et al., 2015 ). However, these studies are only reliable for the diagnosis of acute cases but have limited value in subclinical cases due to low parasitaemia (Alim et al., 2012 ; Hosen et al., 2020 ; Samad et al., 1983 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, it has been reported that approximately 22% of asymptomatic cattle showed seropositive for T. annulata [15]. We also recently reported that approximately 80 and 20% of asymptomatic cattle in Natore and Rajshahi district, Bangladesh, showed seropositive for T. annulata [1]. These reports suggested that asymptomatic infection of T. annulata is common among Bangladesh cattle.…”
mentioning
confidence: 69%
“…To determine whether T. annulata infected cattle exists in Bangladesh, blood samples of fifty-nine asymptomatic cattle, 10 local breeding and 49 mix breeding, were randomely collected from a village in Singra Upazila (a subunit of a district) in the Natore District, Rajshahi Division of Bangladesh from February to April, 2017. There, farmers graze a few dozen local breeding and mix cattle in one place, and we recently reported that some cattle in the village have antibodies reacting with T. annulata surface protein [1]. However, it has not yet confirmed whether these cattle harbor the parasite.…”
mentioning
confidence: 99%
See 1 more Smart Citation